Somaclonal variation in plant adaptation to acid soil in the tropical forage legume Stylosanthes guianensis - Rao, Idupulapati M.; Roca, W.; Ayarza, Miguel Angel; Tabares Z., Eddie; García, R. (Springer, 1992)
Somaclonal variation offers the possibility to obtain changes in one or a few characters of an otherwise outstanding cultivar without altering the remaining, and often unique, part of the genotype. It has been shown to be heritable for some species. A check line of Stylosanthes guianensis (Aubl.) Sw., CIAT 2243 and 14 somaclones in the R4 generation, selected after three generations from the original 114 plants regenerated from callus cultures, were used in a glasshouse trial. The main objective of the study was to evaluate the physiological basis of the differences in agronomic performance of certain somaclones over the check genotype when grown in a sandy loam acid soil at low or high fertility level. Measurements at the time of harvest (170 days of plant age) included dry matter distribution between shoot and roots, leaf area production, nutrient levels in soil and plant parts, and uptake of nutrients from soil. Somaclones differed with the check genotype in terms of (i) partitioning of fixed carbon between the shoot and roots; (ii) root biomass production and (iii) uptake of nitrogen and phosphorus. Positive relationships were found between total nitrogen uptake and total biomass, and total phosphorus uptake and total biomass, and total phosphorus uptake and total nitrogen uptake. The results of this study provide an insight into the potential use of somaclonal variation for the improvement of plant adaptation to acid soil conditions.